2003
DOI: 10.1897/02-553
|View full text |Cite
|
Sign up to set email alerts
|

Binding of perfluorinated fatty acids to serum proteins

Abstract: Abstract-Perfluorooctane sulfonic acid (PFOS) accumulates in the liver and blood of exposed organisms. The potential for these surfactant molecules to interfere with hormone/protein interactions in blood is of concern given the importance of these interactions. The PFOS binding to serum proteins was investigated by assessing its ability to displace a variety of steroid hormones from specific binding proteins in the serum of birds and fishes. Perfluorooctane sulfonic acid had only a weak ability to displace est… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
381
4
4

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 535 publications
(407 citation statements)
references
References 35 publications
18
381
4
4
Order By: Relevance
“…However, involvement of other subtypes of calcium channels cannot be excluded, since PFOS-induced [Ca 2+ ]i increase was not completely blocked by nifedipine. As for the specific mechanism of action, Harada and co-workers (14) deduced that PFOS may directly activate calcium currents at specific lipid (25). PFOS has a sulfonic group attached to the perfluorinated chain, and PFOA has a carboxylic group.…”
Section: Discussionmentioning
confidence: 99%
“…However, involvement of other subtypes of calcium channels cannot be excluded, since PFOS-induced [Ca 2+ ]i increase was not completely blocked by nifedipine. As for the specific mechanism of action, Harada and co-workers (14) deduced that PFOS may directly activate calcium currents at specific lipid (25). PFOS has a sulfonic group attached to the perfluorinated chain, and PFOA has a carboxylic group.…”
Section: Discussionmentioning
confidence: 99%
“…This hypothesis has been supported by studies on free-ranging mammals, including polar bears, which reported no correlation of PFAA concentrations with extractable lipid levels in either liver or plasma samples [12][13][14]. The polar moiety of the PFSA and PFCA molecule preferentially binds with proteins over nonpolar molecules (e.g., free fatty acids), specifically fatty acid binding proteins, lipoproteins, and albumin, and is sequestered into protein-rich tissues such as liver and blood [15][16][17]. Very recently, Cassone et al [18] reported that chicken egg embryos injected with perfluorohexane sulfonate (PFHxS) and perfluorohexanoic acid (PFHxA) had greater accumulation in proteinrich compartments (i.e., yolk sac and liver).…”
Section: Introductionmentioning
confidence: 92%
“…Chain lengths for PFCAs of C 8 to C 15 and for PFSAs of C 6 , C 8 , and C 10 , as well as PFOSAs, were detected above the MLOQ in all brain compartments ( Table 2). All other PFASs were either below the detection limit, detected with low frequency, or detected near the detection limit (Supplemental Data, Table S3).…”
Section: Pfaa Concentration Relationships With Extractable Lipid Contentmentioning
confidence: 99%
See 1 more Smart Citation
“…The tested PFAAs have the ability to compete and displace fatty acids from the protein, and consequently change the distribution between free and bound fatty acids in plasma (Chen and Guo 2009). PFOS was demonstrated to bind strongly to bovine serum albumin (BSA) (Jones et al 2003). Noncovalent interactions of PFOS with BSA alter its secondary conformation, and such changes inhibit the physiological function of BSA to transport vitamin B 2 (Wu et al 2009).…”
Section: Introductionmentioning
confidence: 99%